# How do you solve #(5/(y+5)) = (4/(y-3)) #?

Remove the brackets:

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (5/(y+5)) = (4/(y-3)), you can start by cross-multiplying. Multiply 5 by (y-3) and 4 by (y+5). This gives you 5(y-3) = 4(y+5). Expand the equation by distributing the numbers, which results in 5y - 15 = 4y + 20. Next, isolate the variables by moving all the y terms to one side and the constant terms to the other side. Subtract 4y from both sides, which gives you y - 15 = 20. Then, add 15 to both sides to get y = 35. Therefore, the solution to the equation is y = 35.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you solve #2n-4(n-3)=-(n-2)#?
- How do you graph #R(x) = (x + 2)/(x^2 - 4)#?
- How do you solve #\frac { 1} { y + 3} = \frac { 7} { y - 3} - \frac { 2} { y ^ { 2} - 9}#?
- How do you simplify #(x^2+4x-32)/(x+8)# and what are the ecluded values fot he variables?
- How do you solve #\frac{1}{5} x + 4= 12#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7